2002
DOI: 10.1002/1521-379x(200206)54:6<217::aid-star217>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Pea Starch: Composition, Structure and Properties — A Review

Abstract: Recently, pea has developed into a major protein crop in Western Canada. In the search for new food protein resources, small commercial facilities in Canada have engaged in manufacturing protein concentrates from pea by air classification or wet milling techniques. However, the major products from these processes are either crude or refined pea starches. Pea starch has been utilized almost exclusively for industrial application. A major factor, which has an adverse effect on the widespread utilization of pea s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
219
2
10

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(247 citation statements)
references
References 117 publications
16
219
2
10
Order By: Relevance
“…UP2782 showed the highest value of swelling power while PDW291 showed the least (Table 3). The differences in swelling power of starches may be attributed to the differences in structural properties of starches as this parameter provide the evidence of strength of interaction between starch chains within amorphous and crystalline domains (Ratnayake et al 2002). Swelling power in the range of 8.3 to 10.1 g/g had been reported earlier for starches from different Indian wheat lines (Shevkani et al 2011).…”
Section: Physicochemical Characteristicsmentioning
confidence: 57%
“…UP2782 showed the highest value of swelling power while PDW291 showed the least (Table 3). The differences in swelling power of starches may be attributed to the differences in structural properties of starches as this parameter provide the evidence of strength of interaction between starch chains within amorphous and crystalline domains (Ratnayake et al 2002). Swelling power in the range of 8.3 to 10.1 g/g had been reported earlier for starches from different Indian wheat lines (Shevkani et al 2011).…”
Section: Physicochemical Characteristicsmentioning
confidence: 57%
“…It has been proved that the acid-treatment process incorporated kinds of polar groups with MWCNTs, improved the hydrophilicity of MWCNTs, and reduced agglomerations of MWCNTs. 40 These are greatly contributed to enhance the hydrogen bonding interactions between acid-treated MWCNTs and PS, increase the compatibility between MWCNTs and PS, and result in an improvement of the mechanical performance of the PS/MWCNTs nanocomposite films as discussed later. The nanocomposite materials resulting from the casting and evaporation were studied by WAXD as a function of the MWCNTs content and the corresponding diffractograms are shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…36,37 For instance, introduction of carboxylic, carbonyl, and hydroxyl groups on MWCNTs by refluxing MWCNTs with nitric acid or mixed acid greatly enhanced their interaction with various polymer matrixes, thus improving the mechanical properties of the resulting composites. 38,39 As Ratnayake et al 40 reported, Canada is the largest producer ($ 25% of total world production) and the largest exporter ($ 40% of the total world exports) of field pea in the world. Pea starch and pea protein are the two main products from wet process in the pea industry.…”
Section: Introductionmentioning
confidence: 99%
“…[36] Ratnayke et al concluded that amylose content primarily influences solubility while amylopectin influences the SP. [37] Lipid-amylose complexes, starch chains in amylopectin ratio, molecular weight, and relative distribution of amylose and amylopectin are reported to affect the SP and solubility of starch. [38] The Light transmittance value of starch pastes from different cultivars is presented in Fig.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%